Avaliação do perfil glicêmico de pacientes obesos antes e após cirurgia bariátrica - Lira, José Adelson de (2016)
Background: Bariatric surgery has been a treatment option for morbid obesity and its comorbidities. Results found in literature show a significant reduction in the blood’s glucose levels at the immediate postoperative period and a smaller reduction in a later postoperative period. Objective: This study aimed to evaluate the glycemic profile of patients before and after bariatric surgery. Methodology: This research corresponds to an observational, retrospective and analytical study to evaluate the glycemic profile in obese patients before and after surgery. We conducted a review of medical records of 331 patients undergoing bariatric surgery for bypass technique from January 2009 to April 2016. The following laboratory parameters were used: fasting blood glucose, postprandial blood glucose, insulin, glycosylated hemoglobin (HbA1c), C-peptide and HOMA-IR and two anthropometric, weight and BMI. The data correspond to the preoperative and postoperative (6, 12, 18 and 24 months). Statistical analysis was performed using the nonparametric Kruskal - Wallis was considered statistically significant at p <0.01. Results: The results showed a reduction in the average of all the variables. Weight reduction of 38%. BMI reduction of 36%. Fasting glycemia reduction of 14,5%. Post prandial glycemia reduction of 21,0%. Insulin reduction of 73,5%. HbA1c reduction of 25,9%. C-peptide reduction of 56,2%. HOMA-IR reduction of 22,1%. Conclusions: It is concluded that bariatric surgery has great metabolic benefit especially with regard to normalization of glycemic profile.